The Influence of Instagram on Purchasing Decisions through Brand Awareness (a Study at Hive & Honey Solo) - Nugroho, Melisa Christina; Herdinata, Christian (KnE Social Sciences, 2021)
As the food and beverage industry is growing rapidly, entrepreneurs are using this opportunity to engage in this area of business. Data show that social media is a very useful tool to advertise products or services to attract more customers, and with more and more people using social media, businesses have made social media one of their main marketing strategies. This research aimed to explore the effect of Instagram social media marketing on decisions to purchase Hive & Honey Solo products through brand awareness as a mediating variable. The study had a total of 92 respondents who had purchased Hive & Honey Solo products more than once. Data were collected using a questionnaire with 13 indicators that used the Likert scale, and data were processed using PLS-SEM. Social media marketing significantly positively influenced decisions to purchase Hive & Honey Solo products through brand awareness. Keywords: social media marketing, brand awareness, purchasing decision